Thinking Profile Of Junior High School Students In Understanding The Concept Of Quadrangles With Linguistic Intelligence, Logical-Mathematical Intelligence, And Visual-Spatial Intelligence - Safarudin, Yanuar Mahfudz (Journal of Strategy and Transformation in Educational Management, 2024)
This study aims to describe the thinking profile of junior high school students who understand the concept of quadrilaterals with linguistic, logical, mathematical, and visual-spatial intelligence. This research is a descriptive study with a qualitative approach. The research subjects are three seventh-grade students of MTs Misykat Al-Anwar Kwaron, Diwek, Jombang, East Java. The research began by determining the research subjects using the MIR ( Multiple et al.) instrument. Relatively similar mathematical abilities and the same gender were also considerations for researchers when choosing subjects. Based on the interview guidelines, the researcher interviewed each subject. Data validity checking used time triangulation. Based on the results of the research that has been conducted, it was found that, (i) students with linguistic intelligence when associating information in grouping quadrilaterals based on alphabetical order, and when associating or connecting information in mentioning the properties of the flat shapes, the students pay attention to the sides first even though what is mentioned is different, such as having four sides, opposite sides are the same length, opposite sides are parallel, and when mentioning the definition of the flat shapes, the students use the genetic definition, (ii) students with logical-mathematical intelligence when associating information in grouping quadrilaterals based on simple images according to them, namely starting from rectangles, squares, then the next one is random, and when associating information in mentioning the properties of quadrilaterals, the students consistently start by paying attention to the number of sides, and continue with the following property, when associating information in mentioning the definition, the students mention the properties mentioned before by starting with the word "quadrangle", (iii) students with visual-spatial intelligence when associating information in grouping quadrilaterals based on their sense of sight are focused on shapes that are easy according to them, namely starting with rectangles, squares and so on, when associating information in mentioning the properties of quadrilaterals, the students use teaching aids and mentioning the number of symmetries of the quadrilateral, then randomly mentioning its properties, when relating information in mentioning the definition of the quadrilateral, the student uses the properties that have been mentioned previously, but the subject has difficulty in choosing which property is suitable to represent the definition of the quadrilateral.